The Strategy to Enhance Traveloka's Digital Interaction with Customer Loyalty by Improving E-service Quality and Customer Experience - Ramdani, Rizal; Wardi, Putri Amalia (ProBisnis : Jurnal Manajemen, 2024)
This research aimed to enhance digital interaction with the objective of increasing Traveloka customer loyalty by examining the impact of e-service quality and customer experience. The study employed a purposive sampling method to select 400 respondents of Traveloka users. The respondents were surveyed quantitatively using an explanatory survey method. Structural Equation Modeling (SEM) was employed to evaluate the relationship between variables. The findings indicated that customer loyalty was significantly influenced by customer experience and e-service quality, which were intended to enhance digital interaction on the Traveloka platform. Demographic data indicated that millennials and Gen-Z constitute 80% of consumers, with elevated educational qualifications. Furthermore, the discovery provided theoretical advancements in developing a comprehensive model of digital loyalty, as well as practical implications for improving digital travel platforms. Therefore, this research showed that achieving digital customer loyalty via digital interactions demanded the successful integration of excellent consumer experiences and superior service standards.